Pengembangan Sistem Pendeteksi Tekanan Ban Berbasis Internet of Things untuk Otomatisasi Inspeksi Kendaraan - Benita Aryani; Mokhammad Rifqi Tsani (P3M Politeknik Negeri Cilacap, 2025)
Tire pressure inspection is a crucial procedure at PT HMMI based on the Part Inspection Standard (PIS), with a recommended pressure of 105-125 Psi for buses. Currently, inspections are still performed manually, deemed inefficient and prone to human error. To address this and meet inspection standards, this research aims to develop an Internet of Things (IoT)-based bus tire pressure detection system. The Research and Development (R&D) method was applied to design and build this system. The developed system utilizes a pressure transmitter sensor integrated with an ESP32 microcontroller, equipped with LCD, LED, and buzzer outputs. Pressure measurement data is transmitted in real-time and stored in Google Spreadsheet for paperless documentation. Functional testing of the system on buses demonstrated the sensor's detection capability within 2-3 seconds with all outputs functioning optimally. Accuracy test results showed excellent performance, reaching 99.44% with an average error of only 0.56% after calibration with 30 pressure parameters. This system successfully proved its capability as an effective solution for automatically and accurately monitoring bus tire pressure, supporting the achievement of PIS standards and enhancing the efficiency of inspection processes in the automotive industry.